1999
DOI: 10.1256/smsqj.55709
|View full text |Cite
|
Sign up to set email alerts
|

A model study of corona emission from hydrometeors

Abstract: SummaryThe maximum measured electric fields in thunderclouds are an order of magnitude less than the fields required for electric breakdown of the air. One explanation for lightning initiation in these low fields is that electric breakdown first occurs at the surfaces of raindrops where the ambient field is enhanced very locally due to the drop geometry . Laboratory experiments [Crabb & Latham, 1974] indicate that colliding raindrops which coalesce to form elongated water filaments can produce positive corona … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 3 publications
(4 reference statements)
0
13
0
Order By: Relevance
“…Overall, the results presented here complement the experimental studies mentioned above. The general trend of the decreasing electric field necessary for streamer initiation with increasing hydrometeor length (Figure ) obtained from our study is consistent with the results of these studies, as well as with other previous experimental and theoretical work [e.g., Crabb and Latham , ; Schroeder et al ., ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, the results presented here complement the experimental studies mentioned above. The general trend of the decreasing electric field necessary for streamer initiation with increasing hydrometeor length (Figure ) obtained from our study is consistent with the results of these studies, as well as with other previous experimental and theoretical work [e.g., Crabb and Latham , ; Schroeder et al ., ].…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that the emission of positive coronas from colliding raindrops can readily occur in thunderclouds and therefore be a possible source for triggering lightning. Schroeder et al [] conducted a modeling study of positive corona emission around a simulated coalesced water drop. They modeled positive discharges using a one‐dimensional drift‐diffusion equation, paired with an analytical solution to the electric field.…”
Section: Introductionmentioning
confidence: 99%
“…However, such an electric field intensity is of 1 order of magnitude lower than the electric field threshold required to breakdown cloud air. Therefore, additional ignition mechanisms have been considered, such as runaway electrons (Gurevich et al, 1992) or hydrometeor interactions present in high electric fields (Crabb and Latham, 1974;Coquillat and Chauzy, 1994;Schroeder et al, 1999;Coquillat et al, 2003). Natural lightning flashes then occur when the ambient electric field exceeds a threshold of a few kV m −1 .…”
Section: Introductionmentioning
confidence: 99%
“…The corona appeared when colliding liquid drops form one long coalesced liquid drop. Schroeder et al () developed a model for corona inception from a long coalesced drop and obtained good agreement with experimental observations. This model was further applied for thunderstorm conditions (Solomon et al, ), and the authors concluded that such mechanism cannot alone trigger lightning.…”
Section: Introductionmentioning
confidence: 79%